2004
DOI: 10.1007/s00432-004-0604-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to induction chemotherapy predicts local control and long-term survival in multimodal treatment of patients with locally advanced esophageal cancer

Abstract: Intensive chemoradiation followed by surgery seems to be appropriate to improve long-term survival of high-risk patients with locally advanced esophageal cancer. In our trial, local tumor control and prognosis were best correlated with response to induction chemotherapy. These results may help to guide decisions regarding surgery in multimodal treatment of EC. Further efforts are needed to increase the number of treatment responders and to predict tumors not responding to chemo(radio)therapy earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
0
31
0
4
Order By: Relevance
“…Weight loss of greater than 10 per cent total bodyweight has been associated with adverse outcome on multivariable analysis among patients with oesophageal cancer who had undergone surgical resection and chemoradiotherapy 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss of greater than 10 per cent total bodyweight has been associated with adverse outcome on multivariable analysis among patients with oesophageal cancer who had undergone surgical resection and chemoradiotherapy 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Stahl et al (19,20) reported that the overall survival rate was significantly higher in clinical responders than in nonresponders and that preoperative CRT improved local progression-free survival. Therefore, CRT is expected to serve ONCOLOGY REPORTS 18: 901-908, 2007 905 Table II.…”
Section: Discussionmentioning
confidence: 99%
“…The primary multivariate Cox model included tumor stage and grade (American Joint Committee on Cancer criteria, 7th edition, 2009). Age, sex, and presurgery weight loss (Ն 10%) were added in subsequent models [33][34][35] ; given that results were highly stable, multivariate models containing all covariates are reported. For ever smokers, number of pack-years was also included as indicated.…”
Section: Clinical End Points and Statistical Analysismentioning
confidence: 99%